2002
DOI: 10.1002/jbm.1279
|View full text |Cite
|
Sign up to set email alerts
|

Control of in vivo microvessel ingrowth by modulation of biomaterial local architecture and chemistry

Abstract: We developed a method for controlling local architecture and chemistry simultaneously in biomaterial implants to control microvessel ingrowth in vivo. Porous polypropylene disks (5 mm in diameter and 40 microm thick) were plasma-coated with a fluoropolymer and then laser-drilled with 50-microm-diameter holes through their thickness. We then oxidized the disks to create hydroxyl functionality on the exposed polypropylene (inside the holes). Acrylamide was grafted to the hydroxyl groups through polymerization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…To regenerate bone tissues, the scaffold should have an appropriate pore size and 100% pore interconnectivity, so that pore structure microvascular induction can occur and osteogenesis can be maintained 29, 30. As previously reported, the optimal pore size remains an issue of debate in bone tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…To regenerate bone tissues, the scaffold should have an appropriate pore size and 100% pore interconnectivity, so that pore structure microvascular induction can occur and osteogenesis can be maintained 29, 30. As previously reported, the optimal pore size remains an issue of debate in bone tissue regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…This assessment was based on elevated macrophage, alkaline phosphatase, and acid phosphatase concentrations; however, extracellular protein concentrations did not vary significantly between the PE and ot-PVC. Other cage implant studies have shown that specimen surface chemistry impacts macrophage adhesion, FBGC fusion, apoptosis, microvessel growth, and surface protein expression in vivo [1216]. Of greatest relevance was the study by Brodbeck et al that used the cage implant system to show that material-adherent macrophages express mRNA for cytokines and growth factors such as IL-6, IL-8, IL-10, TGF-β, IL-1β, and IL-13 in a surface chemistry dependent manner [5].…”
Section: Introductionmentioning
confidence: 99%
“…23 According to several researchers, proper pore structure can result in high osteoblastic activities. 24 However, the optimal pore size of the scaffold for bone tissue regeneration has been a debated issue, because the several aspects that affect cellular behavior can be mixed; smaller pore sizes increase the surface area of scaffolds and induce high cell attachment, while larger pore sizes induce easy migration of cells. Although the optimum pore size is not well defined in bone tissue regeneration, in this work, we selected a pore size of 300 mm and square pore shape.…”
Section: Shape Stability and Morphologies Of The Fabricated Biocompos...mentioning
confidence: 99%